Quality of a Chickpea‐Based High Protein Snack. Issue 6 (21st May 2019) - Gupta, Sahil; Liu, Changqi; Sathe, Shridhar K.
Abstract : Abstract: A chickpea‐based high protein, ready‐to‐eat snack was prepared using six chickpea types. The chickpea seeds and their corresponding snack products were analyzed for proximate composition, antinutrients, and select quality parameters. Chickpea types had: lipid (4.25% to 6.98%), moisture (6.63% to 9.15%), protein (23.33% to 30.95%), and carbohydrate (54.60% to 60.40%) contents exhibiting significant ( P ≤ 0.05) differences. Ash content (1.94% to 2.41%) did not register significant differences. Chickpea types did not show variability in either polypeptide profile or in vitro protein digestibility. In the tested seeds, hemagglutinins and α‐amylase inhibitors were not detected, while trypsin (12.73 to 19.58 units/mg sample) and chymotrypsin inhibitors (62.91 to 84.91 units/mg sample) activity varied significantly ( P ≤ 0.05). The chickpea‐based snack product had intermediate‐moisture (23.31% to 27.81%), was low in lipids (5.09% to 5.84%), free of antinutrients, and was a good source of proteins (12.45% to 14.10%), carbohydrates (51.86% to54.96%), and minerals (1.53% to 2.43%). The L *, a *, and b * values of the products ranged from 75.97 to 79.38, 3.46 to 4.75, and 27.65 to 34.65, respectively. The hardness, springiness, and fracturability of the product were 700.89 to 955.23 g, 43.38% to 47.14%, and 5.26 to 5.90 mm, respectively. Practical Application: Development of new bean‐based products, such as a chickpea‐based snack with an overall good nutrition and taste, may play an important role in increasing the consumption of underutilized dry beans in the United States, shown to promote better health and wellness.